Is the Population Growth Affected by the Growth of GDP or vice versa? : The Case of Africa - Mec, Michal; Potužák, Pavel; Kadeřábková, Božena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2020)
The diploma thesis aims to analyse whether GDP growth per capita affects population growth or vice versa. The analysis of the relationship between GDP growth per capita and population growth is done by two models. The Bootstrapped Panel Granger Causality model finds no causality when population growth is a dependent variable and a few cases of causality in Africa for GDP growth per capita as dependent variable. The Dynamic Panel Data model estimates GDP growth per capita as a significant explanatory variable in all cases. Population growth is a significant explanatory variable in all cases except for the situation when the model includes health control variables. Used data for this analysis meets an established conditions for using both models.
Vedoucí práce: Pavel Potužák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses